Development and Verification of an Immune-Related Gene Pairs Prognostic Signature in Hepatocellular Carcinoma - Feng, Xiaofei; Mu, Shanshan; Ma, Yao; Wang, Wenji (Frontiers in Molecular Biosciences, 2021)
With the increasing prevalence of Hepatocellular carcinoma (HCC) and the poor prognosis of immunotherapy, reliable immune-related gene pair (IRGP) prognostic biomarkers are needed for personalized management and treatment of patients. Gene expression profiles and clinical information of HCC patients were obtained from TCGA and ICGC databases. The IRGP is constructed using immune-related genes (IRG) with large variations. The least absolute shrinkage and selection operator (LASSO) regression analysis is used to construct IRGP signature. The IRGP signature is verified through ICGC data. 1309 IRGPs were constructed from 90 IRGs with high variability. We obtained 50 IRGPs that were significantly related to the prognosis and constructed a signature that included 17 IRGPs. In the TCGA and ICGC cohorts, patients were divides into high- and low-risk groups by the IRGP signature. The overall survival time of patients in the low-risk group is longer than that in the high-risk group. After adjustment for clinical and pathological factors, multivariate analysis showed that the risk score is an independent prognostic factor. The Receiver operating characteristic (ROC) curve confirms the accuracy of the signature. Besides, gene set enrichment analysis (GSEA) revealed that the signature is related to immune biological processes, and the immune microenvironment status is different in different risk scores. The proposed IRGP signature is a promising biomarker for evaluating the overall survival of HCC, thus providing new ideas for the diagnosis and treatment of the disease.